PENGARUH KUALITAS LAYANAN SHORT MESSAGE SERVICE (SMS) GATEWAY TERHADAP KEPUASAN PASIEN RAWAT JALAN DI RUMAH SAKIT UMUM DAERAH (RSUD) ARIFIN ACHMAD PROVINSI RIAU - Rika Fitri; Anuar Rasyid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Regional General Hospital (RSUD) Arifin Achmad Riau Province have a service that can help outpatients to facilitate outpatients to create the accuracy and speed of service, especially in terms of registration, namely the SMS gateway service. The purpose of this study was to study most of the quality of SMS gateway services to the satisfaction of outpatients in Arifin Achmad Hospital, Riau Province. . The theory used in this study was the stimulus-response theory.This study used quantitative research methods, with data were collected from distributing questionnaires directly to outpatients with a sample size of 96 which was determined through random sampling technique. The data analysis technique used was simple linear regression analysis techniques.The results showed that the regression coefficient in this study was Y = 4.718 + 0.478 X. The constant number (a) was 4.718 and the variable coefficient X was 0.478. Meanwhile t count (6.377) is greater than the t table of 1.985 with a significance level of 0.000 smaller than α = 0.05. Based on the statistical calculations obtained, Ha was acceptede and Ha was rejected. In conclusion, there was a significant effect of the quality of the gateway SMS service (X) on outpatient satisfaction (Y) at RSUD Arifin Achmad of Riau Province. The correlation coefficient (r) obtained in this study was 0.550.  It means that the relationship between the variable of SMS Gateway Service Quality (X) and the variable of Outpatient Satisfaction was in the moderate category. On the other hand, the coefficient of determination (Rsquared) obtained was 0.320. It means that the outpatient satisfaction of 30.2% was influenced by the quality of SMS gateway service. While the remaining 77.2% is influenced by other variables not included in this study. Keyword: Quality Of Service SMS Gateway, Outpatient Satisfaction, Rumah Sakit Umum Daerah (RSUD) Arifin Achmad Provinsi Riau.